Atrial Fibrillation and Resistant Stroke: Does Left Atrial Appendage Morphology Matter? A Case Report - Sarti, Cristina; Stolcova, Miroslava; Scrima, Giulia Domna; Mori, Fabio; Failli, Ylenia; Accavone, Donatella; Biagini, Silvia; Rapillo, Costanza Maria; Nencini, Patrizia; Mattesini, Alessio; Di Mario, Carlo; Meucci, Francesco (Frontiers in Neurology, 2020)
Introduction: Patients with atrial fibrillation (AF) can experience ischemic stroke despite adequate anticoagulant therapy. The secondary prevention strategy of these so-called “resistant strokes” is empirical. Since about 90% of patients with ischemic stroke due to atrial fibrillation have thrombus in left atrial appendage (LAA) we sought to explore the possibility that resistant stroke could have a LAA morphology resistant to anticoagulants. Case Report: A 77 years old man affected by AF experienced two cardioembolic ischemic stroke while on anticoagulants. The study of LAA showed a windsock-like morphology in the proximal part while distally the LAA presented a cauliflower morphology with a large amount of pectinate muscles and blood stagnation. The precise characteristics of LAA were properly understood integrating images obtained by cardiac CT, transesophageal echocardiography, and selective angiography. A high risky LAA for thrombus formation was diagnosed and its occlusion (LAAO) as an add-on therapy to anticoagulants was proposed and performed. Six month follow-up was uneventfully. Conclusion: The systematic study of LAA in patients with resistant-stroke could help to identify LAA malignant morphology. The efficacy on stroke recurrence of the combined therapy (anticoagulants plus LAAO) is worthy to be tested in randomized trials.